Cultural Mirrors Made of Papier Mâché: Challenging Misrepresentations of Indigenous Knowledges in Education Through Media - Iseke, Judy (Alberta Journal of Educational Research, 2010)
Misrepresentation, appropriation, and denigrating Indigenous knowledge is still common practice in educational institutions despite efforts of critical educators to challenge these practices. One such challenge was to papier mâché totem poles in an education institution’s library in a faculty of education that houses teacher education programs. A papier mâché cross focused attention on the use and misuse of symbols and educated people about the problematic representational practices of papier mâché totem poles and crosses. What are the cultural discourses that support the inclusion of false representations of Indigenous knowledge in an education library? I draw attention to strategies and practices of challenging misrepresentation through the use of Indigenous media in education, examine challenges in changing institutional climates of teacher education, and encourage discussion of how Indigenous knowledge and people can be full partners in educational institutions.